Case Report: Cerebrospinal Fluid Dynamics in the Optic Nerve Subarachnoid Space and the Brain Applying Diffusion Weighted MRI in Patients With Idiopathic Intracranial Hypertension—A Pilot Study - Berberat, Jatta; Pircher, Achmed; Gruber, Philipp; Lovblad, Karl-Olof; Remonda, Luca; Killer, Hanspeter Esriel (Frontiers in Neurology, 2022)
Purpose The aim of this study was to examine the cerebrospinal fluid (CSF) flow rates in the subarachnoid space (SAS) of the optic nerve (ON) and the brain in patients with idiopathic intracranial hypertension (IIH) and papilledema (PE) compared to healthy controls by applying non-invasive diffusion weighted MRI. Methods Retrospective analysis of diffusion weighted MR images of 5 patients with IIH (10 ONs), mean age: 31 ± 10 years, 5 females) and 11 healthy controls (22 ONs, mean age: 60 ± 13 years, 5 females). The flow velocity flow-range ratio (FRR) between the intracranial cavity and the subarachnoid space (SAS) of the ON was calculated in both groups and then compared. Results The mean FRR was 0.55 ± 0.08 in patients with IIH and 0.63 ± 0.05 in healthy controls. The difference between IIH patients and healthy controls was statistically significant (p < 0.05). Conclusions CSF flow velocity was decreased in IIH patients with PE compared to healthy controls. Reduced CSF flow dynamics might be involved in the pathophysiology of PE in IIH and diffusion weighted MRI can be a useful non-invasive tool to study CSF flow dynamics within the SAS ON.